P851 Identifying potential predictive biomarkers from plasma exosomes and adoptive T cells that differentiate short and long-term metastatic nasopharyngeal cancer survivors treated with chemotherapy and virus-specific T cells. (15th April 2020) - Shuen, Timothy; Who-Whong, WANG; Toh, Han Chong; Lim, Janice; Tan, Cherlyn; Kosasih, Jennie; Cheong, Rachael
Abstract : Background: The identification of biomarkers predicting a better outcome to adoptive T cell therapy is an emerging, still nascent field. We previously completed a phase 2 clinical trial of autologous adoptive EBV-specific cytotoxic T lymphocyte (CTL) immunotherapy following gemcitabine + carboplatin chemotherapy as first line treatment in 35 advanced incurable stage 4c nasopharyngeal carcinoma (NPC) patients. Here, we aim 1) to evaluate exosome proteins for potential specific predictive biomarkers of benefit to adoptive T cell therapy and 2) to investigate if a specific immunophenotype of our generated EBV targeting CTLs correlates with survival benefit. Methods: We isolated exosome from plasma samples by size exclusion chromatography and magnetic-based isolation technology, followed by fluorescence-activated cell sorting (FACS) analysis, Western blot analysis for immune-related checkpoint molecules, or mass spectrometry for exosomal peptide detection. All the generated CTLs were analysed by gene expression microarray as well as a FACS system with the use of T cell-specific 23-antibody panel for comprehensive immunophenotyping. The representative CTL samples were also subject to single-cell (sc) RNA-Seq with DNA barcoded antibodies for comprehensive integrated transcriptomics and immunophenotyping analysis. Results: Patients with overall survival longer than 2 years were grouped as long survivors and the remaining patients were grouped as short survivors. Differentially expressed immune-related checkpoint molecules, such as PD1, ICOS, and CD137, were detected in in pre-treatment exosome of long and short survivors. Furthermore, more than 13, 000 high confident and unique peptides which belong to 1, 500 unique proteins were identified and quantified by mass spectrometry from the purified plasma exosome. Pathway enrichment analysis further showed that plasma exosome of the short survivors had significantly higher innate immune response-activating signal transduction-related peptides detected (p-value = 4.81 x 10-5). The transcriptomic analysis revealed that statistically lower expressions of SELL (CD62L) and LEF1 were found in the EBV CTL of the short survivors, suggesting that the EBV CTL of short survivors were characterized by a lesser central memory T cell phenotype. Conclusions: Our data reports that specific pre-treatment plasma exosome proteins, and separately, transcriptomic profile of the generated baseline EBV CTLs prior to infusion into the patients correlate with patient survival, suggesting that they could be used together as biomarkers to predict outcome in the advanced NPC patients treated with this chemo-immunotherapy combination. More in-depth analysis of the immunophenotyping of all the CTLs and the representative CTLs' scRNA-Seq data will be presented at the meeting. Acknowledgements: This work was supported by Singapore government funding (National Medical Research Council (NMRC) – Open Fund - Large Collaborative Grant (OF-LCG) and National Cancer Centre Singapore Block Grant as well as in part by Tessa Therapeutics Ltd.